Evaluation of occupational hazards for nurses in intensive care units of tertiary care centers - Kobra Abdi Zarrini (Journal of Nursing and Midwifery Sciences, 2018)
Context: Nursing is a high-risk occupation, and intensive care units (ICUs) are one of the most sensitive hospital wards. Aim: This study aimed to determine the level of occupational hazards among nurses in the ICUs. Setting and Design: This descriptive-analytical study was conducted on a total of 281 nurses in the ICUs of tertiary care centers in Golestan and Mazandaran Universities of Medical Sciences in 2017. Materials and Methods: Data were collected using a five-dimensional occupational hazard questionnaire. Statistical Analysis Used: Data analysis was performed in SPSS software (version 16) and descriptive and inferential statistics were considered statistically significant (P < 0.05). Results: In this study, 75.1% of the nurses were female and 50.9% of the participants were within the age range of 26–35 years. The total mean and standard deviation of occupational hazards was 3.20 ± 0.66. In addition, the mean values and standard deviations of chemical, ergonomic, biological, psychosocial, and organizational, as well as physical hazards were reported to be 2.43 ± 1.06, 2.6 ± 0.82, 2.63 ± 0.91, 3.38 ± 0.7, and 3.38 ± 0.86, respectively. According to the results, significant differences were observed between occupational hazards and variables of gender, marital status, educational level, and work experience (P = 0.0001). Conclusion: Occupational hazard level was moderate among nurses in the ICUs, and most of the damages were related to the physical dimension. In addition to holding educational workshops in tertiary care centers by the related officials, proper preventive plans must be designed to reduce occupational injuries.